(untitled) (Ameghiniana, 2014)
"A palynological assemblage consisting of twenty-one species of spores, prasinophytes, chlorococcales, acritarchs and chitinozoans has been recovered from the upper section of the Tequeje Formation, Angosto del Beu, northern subandean region, Bolivia. One new combination, Quadrisporites variabilis (Crarner) Ottone n. combo is proposed. Stratigraphic range of previously described species of palynomorphs suggests a late Givetian-early Frasnian age for the assemblage. Correlations with equivalent palynological assemblages from the subandean region of Argentina are proposed."